Clinical development methodology for infusion-related reactions with monoclonal antibodies - Doessegger, Lucette (Clin Transl Immunology, 2015)
Infusion-related reactions (IRRs) are common with monoclonal antibodies (mAbs) and timely related to drug administration and have been reported as anaphylaxis, anaphylactoid reactions and cytokine release syndrome, among other terms used. We address risk management measures for individual patients and for the study and propose a consistent reporting approach in an attempt to allow cross-molecule comparisons. Once the symptoms of IRR have resolved, the mAb may be restarted. Rechallenge should not be done for suspected IgE-mediated anaphylaxis and Grade 4 IRRs. Management of IRRs for subsequent patients includes administration of premedication, which, however, does not prevent IgE-mediated anaphylaxis. Reporting approach: (1) Report as IRRs, reactions occurring during or within 24 h after an infusion. Negative skin Prick test and absent or undetectable allergen-specific IgE levels have high negative predictive value for an IgE-mediated allergic reaction. If IgE-mediated anaphylaxis is suspected based on medical history and/or laboratory test results, the reaction should be reported as suspected (IgE mediated) anaphylaxis. (2) Collect signs and symptoms with grades to allow characterization of IRRs. IRRs pathogenesis is of scientific interest and has impact on drug development. Animal toxicology studies are neither predictive of severe IRRs nor of anaphylaxis in human. Preclinical tests should be further developed to identify patients at risk for severe IRRs, for complement activation-related pseudoallergy and for IgE-mediated anaphylaxis. The proposed approach should help standardizing data collection and analysis of IRRs in an attempt to enable comparisons across molecules.